Nutrient composition and seasonal availability of local feedstuffs for pigs in western Kenya - Carter, Natalie A.; Dewey, Catherine E.; Lukuyu, Ben A.; Grace, Delia; Lange, C.F.M. de (Agricultural Institute of Canada, 2015)
In this study, nutritional values and seasonal availability were estimated for 25 local feedstuffs for pigs in western Kenya, based on analyzed nutrient contents and a review of the literature. Characteristics considered included: crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), ether extract (EE), Ca, P, standardized total tract digestible (STTD) P, total Lys, standardized ileal digestible (SID) Lys (all as g kg−1 of DM), and digestible energy (DE) (kcal kg−1 DM). Contents of total Lys, SID lysine, STTD P, and DE were estimated. Overripe improved-variety avocado (Persea americana) had the greatest estimated DE (5280 kcal kg−1 DM) and EE content (521 g kg−1 of DM). Cattle rumen content had the greatest NDF content (664 g kg−1 of DM). Sun-dried fish (Rastrineobola argentea) had the greatest estimated STTD P content (13.5 g kg−1 of DM). Amaranthus spinosus L. had the greatest Ca content (26 g kg−1 of DM). Fresh cattle blood had the greatest CP and estimated SID Lys content (944 and 83.0 g kg−1 of DM, respectively). Feedstuffs availability periods are: March through May plus September and October; June through August; and November through February. Local feedstuffs of sufficient nutritional value for pigs are seasonally available. Estimated nutritional values may assist in diet formulation.